STRATEGI BERTUTUR DALAM TINDAK TUTUR EKSPRESIF BAHASA INDONESIA PADA KEGIATAN DISKUSI - Alfioda, Tia; Manaf, Ngusman Abdul; Arief, Ermawati (Universitas Negeri Padang, 2016)
ABSTRACTÂ The purpose of this research is describe the shape and strategy in activities of the discussion in class VIII SMP Negeri 3 Padang. This type of research is a qualitative method descriptive. Data in this study is the shape and strategy of said expresive of students is a discussion activity. Based on the findings of research, we can conclude things here. There are six of the said thisplays used students in the discussion, which is say thank you, to say i am sorry, praising, criticizing, angry and complaining. The six of the said expressive was told by using four strategies are recalled, namely speak frankly without a word, speak frankly with a word modesty of the positive, speak frankly with further good manners and speak vaguely in the discussion. The conclusion of this research is that thereâ€™s six of the said displays by using for strategies renakedÂ Kata kunci: ekspresif, strategi, konteks, diskusi